PENINGKATAN KETERAMPILAN MENULIS SURAT DINAS MENGGUNAKAN METODE INKUIRI SMP NEGERI 1 SELIMBAU - Jumiati, .; ., Syambasril; Hanye, Paternus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe background of this research is the lack of writing skill, the minimum of understanding about writing and the low of students learning results. And what is more, the students got lack of experience and knowledge in writing official letter. Furthemore, to improve the skill in writing official letter to VIII B Grade Students of SMP Negeri 1 Selimbau, the researcher used the inquiry method. This research is Class Action Research which is coundected in two cycles. The method used in this research is descriptive qualitative. The result of students learning before conducting Class Action Research is in average of 58,70. Afterwards, the result of students learning in cycle I is in average of 64,52. Furthermore, the score in cycle II is increased in average of 71,04. Then, it can be concluded that this classroom action research using inquiry method had improved students’ writing skill in writing official letter. Keywords: Writing Skill, Official Letter, Inquiry Method